Extragalactic Astrophysics With Next-Generation CMB Experiments - De Zotti, Gianfranco; Bonato, Matteo; Negrello, Mattia; Trombetti, Tiziana; Burigana, Carlo; Herranz, Diego; López-Caniego, Marcos; Cai, Zhen-Yi; Bonavera, Laura; González-Nuevo, Joaquin (Frontiers in Astronomy and Space Sciences, 2019)
Planck